The influence of intellectual capital and total asset turnover on financial distress in manufacturing companies listed on the Indonesian Stock Exchange 2021-2023 - Ila Fadila Putri; Muchriana Muchran (IECON: International Economics and Business Conference, 2024)
This research aims to analyze the relationship between intellectual capital and total asset turnover on financial distress in manufacturing companies listed on the Indonesian stock exchange. Companies today face increasingly competitive competition and unpredictable economic changes. The company will be greatly affected by this, especially because the company’s costs will increase. Companies that cannot compete with other businesses will experience a decline in financial distress, which can cause the company to experience financial distress. A company experiencing financial distress is known as a financial distress. According to Platt and Platt (2007), financial distress is a phase of financial decline that oocurs before bankruptcy or company liquidation. This research method using data analysis techniques, namely descriptive statistical techniques. This research examines the influence of intellectual capital and total asset turnover on financial distress in manufacturing companies listed on the Indonesian Stock Exchange in 2021-2023. The results of this research reveal that there is an influence between intellectual capital has a significant negative effect on financial distress and there is an influence of total asset turnover has a significant positive effect on financial distress in manufacturing companies in 2021-2023. As seen in the table above, Fcount 86,144 > Ftable 3,25. With sig 0,000 < 0,05. Shows that intellectual capital and total asset turnover have a significant effect on financial distress.